Elective neck dissection versus watchful waiting in the management of early tongue cancers with node negative neck: our experience of 68 cases - Gupta, Anchal; Sharma, Rupali; Kalsotra, Gopika; Manhas, Arun; Raj, Dev (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Background: Prognosis for tongue squamous cell carcinoma depends upon lymph node metastasis and the treatment plan depends upon the management of cervical lymph node metastasis. Methods: A prospective analysis of early squamous cell carcinoma oral tongue was done February 2017 to February 2020 in previously untreated and biopsy proven patients with T1-2N0 cancer of tongue and patients with clinically negative nodes on the basis of palpation, ultrasound and computerized tomography (CT) and previously untreated and biopsy proven patients with T1-2N0 cancer of oral cavity. After proper work up, patients were divided into two groups. Group 1 (n=35) patients that underwent a surgical excision of primary tumor with 15mm safe margin and selective neck dissection (level I, II, III), group 2 (n=33) patients that underwent surgical excision of primary tumor with 15 mm safe margin and neck observation. All patients with tumor thickness ≥4 mm were included in this group. Results: The study included 51 (75%) males and 17(25%) female patients. In this study, recurrence was significantly related to tumor thickness (p<0.05) i.e., >4 mm tumor thickness showed significantly higher local recurrence and nodal recurrences. Also, a significantly higher relationship was seen between nodal recurrence and postoperative close surgical margins (p<0.05). Conclusions: Elective neck dissection becomes necessary in patients with T2N0 tumors and tumor thickness of >4 mm as frequency of occult metastasis and recurrence is more in these patients.